Heat Transfer through Porous Media in the Counterflow Regime of He II - Maekawa, R; Baudouy, B (AIP conference proceedings, 2004)
Experimental results are presented for He II counter flow through Al2O3 porous media. Tests have been performed on three porous disks with different thicknesses, 2, 3 and 4 mm, having the same porosity of 32 %, average pore diameter of 2 mum and permeability in the range of 10-14 m2. Temperature and pressure differences were measured across porous media from 1.4 K to 2.1 K in the saturated superfluid helium. The influence on the porous media thickness to the heat transfer is clearly seen on the typical linear Darcy regime and the turbulent Gorter-Mellink regime. Deviation from these classical laws is observed for large temperature difference that can be attributed to the change of He II heat transfer properties due to the complex flow paths of porous media. The effect of porous media thickness to the He II heat transfer is discussed.